Recent Developments in Electrochemical Sensors for the Detection of Antibiotic-Resistant Bacteria - Madhu, Sekar; Ramasamy, Sriramprabha; Choi, Jungil (Pharmaceuticals, 2022)
The development of efficient point-of-care (POC) diagnostic tools for detecting infectious diseases caused by destructive pathogens plays an important role in clinical and environmental monitoring. Nevertheless, evolving complex and inconsistent antibiotic-resistant species mire their drug efficacy. In this regard, substantial effort has been expended to develop electrochemical sensors, which have gained significant interest for advancing POC testing with rapid and accurate detection of resistant bacteria at a low cost compared to conventional phenotype methods. This review concentrates on the recent developments in electrochemical sensing techniques that have been applied to assess the diverse latent antibiotic resistances of pathogenic bacteria. It deliberates the prominence of biorecognition probes and tailor-made nanomaterials used in electrochemical antibiotic susceptibility testing (AST). In addition, the bimodal functional efficacy of nanomaterials that can serve as potential transducer electrodes and the antimicrobial agent was investigated to meet the current requirements in designing sensor module development. In the final section, we discuss the challenges with contemporary AST sensor techniques and extend the key ideas to meet the demands of the next POC electrochemical sensors and antibiotic design modules in the healthcare sector.
Keywords: antibiotic susceptibility testing; antibiotic-resistant; bacteria; electrochemical sensor; nanomaterials